(3GdJhLjgGJ GdMOjKI dEbJUGOjGJ GdJCejf UjQaI GdJCejf s - (3CMeO(B, (3HhTfGaIs ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2019)
(3JfGhd gPG GdcJGH (B"(3GdJhLjgGJ GdMOjKI dEbJUGOjGJ GdJCejf UjQaI GdJCejf(B" (3MjK JMOK Yf eGgjI GdJCejf hVQhQJg dJMbjb JfejI GbJUGOjI hGLJeGYjI , hYf CKQ GdJWhQGJ GdGbJUGOjI GdYGdejI Ydi CShGb GdJCejf , HGdGVGaI Edi OhQ UjQaI GdJCejf aj JWhjQ hYUQfI Shb GdJCejf, haj GdCNjQ bOe JLQHI GdLRGFQ hebGQfJgG eY JLGQH HYV GdOhd(B.s
(3eQGLY U(B.215s
Keywords: (3GdJCejf (B- (3GdHfhcs